Salt-Tolerant Phenomena, Sequencing and Characterization of a Glyoxalase I (Jojo-Gly I) Gene from Jojoba in Comparison with Other Glyoxalase I Genes - Heba Allah A. Mohasseb; Mohei El-Din Solliman; Ibrahim S. Al-Mssallem; Mohammed M. Ba Abdullah; Ahmed Saud Alsaqufi; Wael F. Shehata; Hany A. El-Shemy (Plants, 2020)
Plant response to salt stress and the mechanism of salt tolerance have received major focus by plant biology researchers. Biotic stresses cause extensive losses in agricultural production globally, but abiotic stress causes significant increase in the methylglyoxal (MG) level of GlyoxalaseI (Gly I). Identification of salt-tolerant genes when characterizing their phenotypes will help to identify novel genes using polymerase chain reaction (PCR) to amplify the DNA coding region for glyoxalase I. This method is specific, requiring only genomic DNA and two pairs of PCR primers, and involving two successive PCR reactions. This method was used rapidly and easily identified glyoxalase I sequences as salt-tolerant genes from Jojoba (Simmondsia chinensis (Link) Schneider). In the present study, the glyoxalase I gene was isolated, amplified by PCR using gene-specific primers and sequenced from the jojoba plant, then compared with other glyoxalase I sequences in other plants and glyoxalase I genes like in Brassica napus, ID: KT720495.1; Brassica juncea ID: Y13239.1, Arachis hypogaea; ID: DQ989209.2; and Arabidopsis thaliana L, ID: AAL84986. The structural gene of glyoxalase I, when sequenced and analyzed, revealed that the uninterrupted open reading frame (ORF) of jojoba Gly I (Jojo-Gly I) spans 775 bp, corresponding to 185 amino acid residues, and shares 45.2% amino acid sequence identity to jojoba (Jojo-Gly I). The cloned ORF, in a multicopy constitutive expression plasmid, complemented the Jojo-Gly I, confirming that the encoded Jojo-Gly I in jojoba showed some homology with other known glyoxalase I sequences of plants.